THE MOLECULAR BEHAVIORS OF CALIXARENES AT THE AIR-WATER INTERFACE: DENSITY FUNCTIONAL THEORY, SURFACE PRESSURE, POTENTIAL, AND EFFECTIVE DIPOLE MOMENT - Supian, Faridah Lisa; Wong, Yeong Yi; Abd Karim, Nur Farah Nadia; Radzwan, Afiq; Lim, Darvina Choo Kheng; Al Naim, Abdullah Faisal (Malaysian Journal of Science (MJS), 2022)
This study examined the behaviors of Langmuir-Blodgett ultrathin calixarene films at the air-water interface. The Langmuir trough was used to estimate the surface pressure, surface potential, and effective dipole moment of two calixarenes, namely, calix[4]arene (THC4) and calix[8]arene (THC8). The band gap was determined using the density functional theory (DFT). The DFT simulation gave a band gap of 2.28 eV for THC4, confirming that THC4 was an insulator. The surface pressure isotherms of THC4 and THC8 yielded the expected molecular behavior from the gaseous to the solid phases. THC4 and THC8 showed a perpendicular and a parallel orientation in the air-water subphase, respectively. The ∆Vmax values of TCH4 and THC 8 were 205 mV and 141mV, respectively, and their µ﬩max values were 0.147 D and 0.088 D, respectively.